Hepatic mRNA expression of histone (H3): an early predictor of tumorgenic changes in chronic hepatitis C - El Bassiouny, Azza; Abou-Shousha, Tarek; Moussa, Mona; El-Ahwany, Eman; El-Bassiouni, Nora; Maher, Kesmat; Galli, Ayman; Youssef, Magdy; Zada, Suher (Archives of Medical Science, 2009)
Introduction: Infection with hepatitis C virus (HCV) persists in most infected individuals and can lead to the development of chronic hepatitis, cirrhosis and hepatocellular carcinoma (HCC). Histones are numerous DNA-binding proteins that control the level of DNA condensation and play a critical role in the dynamic changes that occur during the cell cycle. The aim of this study is to assess the changes of histone 3 (H3) mRNA cell cycle gene expression as early predictor of tumorgenic changes in chronic hepatitis C (CHC). Material and methods: The study was conducted on liver biopsies from fifty patients with CHC and HCC. Ten normal liver biopsies taken during surgical cholecystectomy served as controls. Histone H3 mRNA expression was evaluated in formalin- fixed and paraffin-embedded liver tissue sections by in situ hybridization. Results: Out of the fifty cases, 20 cases were diagnosed as CHC, 10 cases with HCV-induced liver cirrhosis and 20 cases as HCC on top of HCV. Hepatic expression of histone H3 was higher in CHC or HCC patients than in control group. The cytoplasmic expression of H3 was higher in HCC and cirrhotic liver disease, while the nuclear expression of H3 was more prominent in CHC especially lower scores of necro-inflammatory activity and fibrosis. Conclusions: It could be concluded that alterations of hepatic expression of histone H3 mRNA quantitatively (increased expression) and qualitatively (nuclear-cytoplasmic shift) may be used for early prediction of tumorgenic changes in CHC.